The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ange.201907388
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Release of Dihydroartemisinin for Synergistic Cancer Therapy Using a CaCO3 Mineralized Metal–Organic Framework

Abstract: Dihydroartemisinin (DHA) has attracted increasing attention as an anticancer agent. However,using DHA to treat cancer usually depends on the synergistic effects of exogenous components,a nd the loss of DHA during delivery reduces its effectiveness in cancer therapy. Reported herein is ap rogrammed release nanoplatform of DHA to synergistically treat cancer with aF e-TCPP [(4,4,4,4-(porphine-5,10,15,20-tetrayl) tetrakis(benzoic acid)] NMOF (nanoscale MOF) having aC aCO 3 mineralizedc oating, whichp revents DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…For the past few years, traditional herbal medicines have generated many chemotherapy drugs which could inhibit a variety of tumor entities [ 5 ]. For instance, dihydroartemisinin (DHA), one derivative of artemisinin, has been proved to possess a potent and broad anti-tumor effect in addition to anti-malarial [ 6 9 ]. However, some existing problems, for example strong hydrophobicity, nonspecific distribution, and rapid elimination from the body, impede the application of DHA in cancer treatment [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, traditional herbal medicines have generated many chemotherapy drugs which could inhibit a variety of tumor entities [ 5 ]. For instance, dihydroartemisinin (DHA), one derivative of artemisinin, has been proved to possess a potent and broad anti-tumor effect in addition to anti-malarial [ 6 9 ]. However, some existing problems, for example strong hydrophobicity, nonspecific distribution, and rapid elimination from the body, impede the application of DHA in cancer treatment [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The nanostructures that can be responsive to peculiar tumor microenvironment (TME) not only possess high functionality and selectivity, but also insignificant invasiveness. [10][11][12][13][14][15][16][17][18][19][20][21][22] Unluckily, the therapeutic efficacy of CDT is confined due to the inadequate Fenton reaction efficiency in weakly acidic TME, on account of the rigorous Fenton reaction condition, limiting its further biological applications. [23][24][25][26] As a consequence, how to increase the therapeutic efficacy of Fenton reaction in tumor is the primary problem of CDT at present.…”
mentioning
confidence: 99%
“…The ROS generation in cells was evaluated by selecting 2 0 ,7 0 -dichlorodihydrouorescein diacetate (DCFH-DA) as a uorescent probe. 47 Corresponding confocal laser scanning microscopy (CLSM) images of Hela cells treated with CuFe-LDHs and GOD/CuFe-LDHs at pH ¼ 7.4 and 6.5 were acquired (Fig. 4D), and the results revealed that cells treated with GOD/CuFe-LDHs at pH ¼ 6.5 exhibited the strongest uorescence signal, indicating the highest ROS production.…”
Section: Resultsmentioning
confidence: 98%